PENGEMBANGAN PEMBELAJARAN EKONOMI DENGAN PEMANFAATAN MEDIA INTERNET - Riza Damayanti; R Gunawan Sudarmanto; Darsono Darsono (Faculty of Teacher Training and Education, University of Lampung, 2013)
The aim of this research is to know the real condition of Economics Learning today which is related planning of learning, teacher work performance, activities students, development of source learning, evaluation of learning, produce of design learning at Senior High School, and to know the effective of using internet in economics learning it grade X, semester I. Design of research which is used is Research and Development (RD), by following the Dick Carey.The result of development research can be concluded: First, development economics learning by internet as source learning, that situation and condition school effected in doing learning to the students as learning subjects.Second, design learning if done by steps as follow; (1) Pre learning, in this step meant to give motivation to the students before doing learning so it makes a fun learning and it makes an interaction among students and teachers. (2) Strategy learning, in this step purposed in learning process has good interaction among students and interactive communication. (3) Collecting data, is done to get the accurate data. (4) Analyze data, in this step, data which is got is analyzed for hypothesis testing. (5) Hypothesis, is done to get the truth from information which is got, and based on collecting data and analyze data. (6) Conclusion, is done the students so the students have the abilities to say the result of findings from the results of hypothesis testing.Third, the using of economics learning by internet more effective than economics learning by conventional.Key words: Economic Learning, Internet Media, Design